Triose-phosphate isomerase deficiency is associated with a dysregulation of synaptic vesicle recycling in Drosophila melanogaster - Stone, Aelfwin; Cujic, Oliver; Rowlett, Angel; Aderhold, Sophia; Savage, Emma; Graham, Bruce; Steinert, Joern R. (Frontiers in Synaptic Neuroscience, 2023)
Numerous neurodegenerative diseases are associated with neuronal dysfunction caused by increased redox stress, often linked to aberrant production of redox-active molecules such as nitric oxide (NO) or oxygen free radicals. One such protein affected by redox-mediated changes is the glycolytic enzyme triose- phosphate isomerase (TPI), which has been shown to undergo 3-Nitrotyrosination (a NO-mediated post-translational modification) rendering it inactive. The resulting neuronal changes caused by this modification are not well understood. However, enhanced glycation-induced cytotoxicity has been reported, thus potentially causing neuronal and synaptic dysfunction via compromising synaptic vesicle recycling. This work uses Drosophila melanogaster to identify the impacts of altered TPI activity on neuronal physiology, linking aberrant TPI function and redox stress to neuronal defects. We used Drosophila mutants expressing a missense allele of the TPI protein, M81T, identified in a previous screen and resulting in an inactive mutant of the TPI protein (TPIM81T, wstd1). We assessed synaptic physiology at the glutamatergic Drosophila neuromuscular junction (NMJ), synapse morphology and behavioural phenotypes, as well as impacts on longevity. Electrophysiological recordings of evoked and spontaneous excitatory junctional currents, alongside high frequency train stimulations and recovery protocols, were applied to investigate synaptic depletion and subsequent recovery. Single synaptic currents were unaltered in the presence of the wstd1 mutation, but frequencies of spontaneous events were reduced. Wstd1 larvae also showed enhanced vesicle depletion rates at higher frequency stimulation, and subsequent recovery times for evoked synaptic responses were prolonged. A computational model showed that TPI mutant larvae exhibited a significant decline in activity-dependent vesicle recycling, which manifests itself as increased recovery times for the readily-releasable vesicle pool size. Confocal images of NMJs showed no morphological or developmental differences between wild-type and wstd1 but TPI mutants exhibited learning impairments as assessed by olfactory associative learning assays. Our data suggests that the wstd1 phenotype is partially due to altered vesicle dynamics, involving a reduced vesicle pool replenishment, and altered endo/exocytosis processes. This may result in learning and memory impairments and neuronal dysfunction potentially also presenting a contributing factor to other reported neuronal phenotypes.